Maternal–foetal transfer of severe acute respiratory syndrome coronavirus 2 antibodies among women with and those without HIV infection. (1st November 2022) - Nunes, Marta C.; Jones, Stephanie; Ditse, Zanele; da Silva, Kelly; Serafin, Natali; Strehlau, Renate; Wise, Amy; Burke, Megan; Baba, Vuyelwa; Baillie, Vicky L.; Nzimande, Ayanda; Jafta, Nwabisa; et al.
Abstract : In pregnant women, antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein cross the placenta and can be detected in cord-blood at the time of delivery. We measured SARS-CoV-2 full-length antispike IgG in blood samples collected from women living with HIV (WLWHIV) and without HIV when presenting for labour, and from paired cord-blood samples. Antispike IgG was measured in maternal blood at delivery on the Luminex platform. Cord-blood samples from newborns of women in with detectable antispike IgG were analysed. The IgG geometric mean concentrations (GMCs) and the percentage of cord-blood samples with detectable antispike IgG were compared between WLWHIV and without HIV. A total of 184 maternal and cord-blood pairs were analysed, including 47 WLWHIV and 137 without HIV. There was no difference in antispike GMCs between WLWHIV and without HIV [157 binding antibody units (BAU)/ml vs. 187 BAU/ml; P = 0.17)]. Cord-blood samples from newborns of WLWHIV had lower GMCs compared with those without HIV (143 vs. 205 BAU/ml; P = 0.033). Cord-to-maternal blood antibody ratio was 1.0 and similar between the two HIV groups. In WLWHIV, those who were 30 years old or less had lower cord-to-maternal blood antibody ratio (0.75 vs. 1.10; P = 0.037) and their newborns had lower cord-blood GMCs (94 vs. 194 BAU/ml; P = 0.04) compared with the older women. Independently of maternal HIV infection status, there was efficient transplacental transfer of antispike antibodies. The GMCs in cord-blood from newborns of WLWHIV were lower than those in HIV-unexposed newborns.